Resiliency oriented integration of DSRs in transmission networks - Soroudi, Alireza; Maghouli, Pouria; Keane, Andrew (IET generation, transmission & distribution, 2017)
Secure and reliable operation of power system in normal and contingency conditions is of great importance for system operator. Natural disasters can seriously threaten power systems' normal operation with catastrophic consequences. While hardening approaches may be considered for resiliency improvement, an application of a new and cost-effective technology is proposed in this study. A planning procedure is proposed for integrating distributed series reactors (DSR)into transmission grids for improving the resiliency against these disasters. DSRs are able to control power flows through meshed transmission grids and thus improve the power transfer capability and the penetration level of renewable generation. The problem of integrating DSRs into transmission grids is formulated as a mixed integer linear programming problem. Different load and wind profiles and a predefined number of disaster scenarios are considered in evaluating the impacts of DSRs on system's operational costs, wind curtailment and load shedding during disasters and normal condition. The uncertainty of wind generation can affect economic viability of DSRs deployment which is handled using information gap decision theory. It is implemented on the IEEE-RTS 24-bus test system and results show the functionality of DSRs in converting the conventional transmission grid into a flexible and dispatchable asset.